A Social Network-Based Peer-To-Peer Model For Resource Discovery - Modarresi, Amir (2009)

(untitled)
Peer-to-Peer (P2P) systems are distributed systems consisting of interconnected nodes which provide scalability, fault tolerance, decentralized coordination, self-organization, anonymity, distributed resources and services sharing, lower cost of ownership and better support for creating ad hoc networks. Data sharing, a subset of resource sharing, is one of the attractive topic in P2P systems. Because of autonomy of the nodes, decentralized coordination and volatility of network caused by the autonomy, data sharing is not an easy task in P2P system. Furthermore, there is no guarantee that a node stays in the network for a specific period of time. Hence, the answers to a particular query may be retrieved from different nodes every time. Moreover, the lack of centralized coordinators makes this process harder. These problems in P2P systems lead to a well known problem which is called resource discovery.